The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1093/icvts/ivs219
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous dilatation of right inferior pulmonary vein stenosis following single-lung transplant

Abstract: We present a 62-year old male who underwent right single-lung transplantation. An autologous pericardial rim was constructed at implantation, as there was insufficient donor atrial cuff. The patient was discharged home but deteriorated over 12 months resulting in oxygen dependency. Computed tomography scan showed stenosis of the right inferior pulmonary vein. The patient underwent pulmonary vein angioplasty under general anaesthesia in September 2007, which was successful and resulted in significant improvemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…(Table1) [3][4][5][6][7][8]11,12 . Most common clinical presentations were respiratory insufficiency, pulmonar y edema or pleural effusion.…”
Section: Discussionmentioning
confidence: 99%
“…(Table1) [3][4][5][6][7][8]11,12 . Most common clinical presentations were respiratory insufficiency, pulmonar y edema or pleural effusion.…”
Section: Discussionmentioning
confidence: 99%
“…Mydin et al described the case of a 62-year-old man who had right PVS following a single-lung transplantation for IPF [ 6 ]. In this case, balloon angioplasty was performed, but stenting was unsuccessful due to technical issues, and the patient’s symptoms recurred after two months [ 6 ]. Gaubert et al reported a patient with left pulmonary artery stenosis, which recurred with balloon angioplasty alone [ 7 ].…”
Section: Discussionmentioning
confidence: 99%